Prarancangan Pabrik Asam Sulfat dari Sulfur dan Udara Kapasitas 310.000 Ton/Tahun - Annas, Muhammad Khoirun, Tri Widayatno,S.T., MS.c., Ph.D, Ir. Nur Hidayati, M.T., Ph.D (2016)
The manufacturer of sulphuric acid purpose to fulfill the domestic demand. This manufacturer of sulphuric acid was planned to be established in 2018 in the Industry Area of Banyuwangi, East Java. This plant was planned to produce sulphuric acid 98% wt capacity 310.000 tons/year usethe raw materials of sulphur (granule) as much as 11.867,9804 kgs/hrandairas much as 81.817,2267 kgs/hr. The process to make sulphuric acid in gas phase with operation condition are 436-551oC and 1,5 atm with irreversible and eksoterm rection. Reactor that used wasfixed bed single tube reactor with 4 numbers of bed andcatalystha used was V2O5 (vanadium pentaoxide). Utility unit consist of sanitation water upply unit as much as 1.684,2083 kgs/hr, proccess water supply unit as much as9.689,0813 kgs/hr, cooling water supply unit as much as 74.620,1277 kgs/hr.Power needed wassupply from PLN about 1000 kWh. Fixed capital needed is aboutIDR686.038.500.423 and working capital is aboutIDR 130.080.548.348. Based on the economic analys, profit before taxes is IDR 213.900.820.166/yearand profit after taxes (25%) is IDR 171.120.656.133/year. Persen Return On Investment (ROI) before taxes 31,18%, and after taxes 24,94%. Meanwhile, Pay Out Time (POT) before taxes is 3,11 yearand after taxes is 3,85 year. Break Event Point amounts 44,71% and Shut Down Point amounts 21,66%. While, iscounted Cash Flow is counted amounts 37,30%. Based on the calculation of the economic analysis, it can be concluded that this manufacturer is reasonable to establish.